2019
DOI: 10.1002/masy.201700082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Branches on the Isothermal Crystallization of Copolymers Based on Poly(ϵ‐caprolactone)

Abstract: A linear poly(ϵ‐caprolactone), PCL, and grafted copolymers based on poly(2‐hydroxyethylmethacrylate) and poly(ϵ‐caprolactone) are used to study the effect of branches on PCL crystallization process. Copolymers are synthetized by a combination of ring opening polymerization and reversible addition fragmentation chain transfer polymerization, showing molar masses between 32 000 and 46 000 g mol−1 with Mw/Mn lower than 1.19. Isothermal crystallization kinetic is performed by Differential Scanning Calorimetry comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…reported that at a small degree of supercooling regime I kinetic is operative and primary nucleation as surface nucleation completed rapidly over the surface and dominated by secondary nucleation for crystal growth. Ninago et al [13] . are reported increase in K g and G 0 of 2 fold and 51 fold respectively for PCL‐g‐HEMA copolymer than pure PCL, indicating decrease in overall mobility of PCL chains due to major confinement, which reduces their final crystallization capacity.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…reported that at a small degree of supercooling regime I kinetic is operative and primary nucleation as surface nucleation completed rapidly over the surface and dominated by secondary nucleation for crystal growth. Ninago et al [13] . are reported increase in K g and G 0 of 2 fold and 51 fold respectively for PCL‐g‐HEMA copolymer than pure PCL, indicating decrease in overall mobility of PCL chains due to major confinement, which reduces their final crystallization capacity.…”
Section: Resultsmentioning
confidence: 97%
“…Ninago et al . have studied that branches of poly(2‐ hydroxyethylmethacrylate) (PHEMA) hinder the formation of PCL crystallites by increasing final crystallization time in case of PCL/PHEMA graft copolymer [13] . In a study by Nie et al [21] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations